Optimizing Cash Waqf and Cash Waqf Linked Sukuk : The Role of Nazhir and The Strategies - Afief El Ashfahany; Novita Lestari (IQTISHADIA, 2022)
This study aims to explore the role and strategy of Nazhir in optimizing the management of cash waqf and cash waqf linked Sukuk (CWLS) yields. The method of the study is field research with a qualitative descriptive approach. The data was obtained through an in-depth interview with key persons from the Central Java Muhammadiyah (PWM Central Java) Waqf and Assets Council, the Nahdlatul Ulama Amil Zakat Institute (LAZISNU), and the Baitulmaal Muamalat. The results of this study emphasize the critical role of Nazhir in managing cash waqf and CWLS yield funds to be distributed to Mauquf 'Alaih. The management of cash waqf by the Central Java Muhammadiyah Waqf and Treasurer Council is carried out in the productive business sector, such as rental equipment, farm investment, and integrated farms in Wonolopo Central Java. Meanwhile, apart from effective businesses, LAZISNU and Baitulmaal Muamalat manage Cash Waqf through the CWLS scheme. The cash waqf yields from the three institutions were channeled to the fields of education, economy, and health. Especially for the CWLS scheme, with the great potential that the combination of cash waqf and Sukuk can be more optimally used as an instrument of financing sources to increase the welfare of people in need, especially during the pandemic.